2021
DOI: 10.1051/ro/2021012
|View full text |Cite
|
Sign up to set email alerts
|

Which group should governmental policies target? Effects of incentive policy for remanufacturing industry

Abstract: Although previous research ignores other subsidy groups, we conduct a comprehensive study. In our closed-loop supply chain (CLSC) model, the manufacturer can produce either new products or remanufactured products of end-of-life (EOL) products recycled by independent recyclers. Our core objective is to explore the pricing strategies of the two products under different government subsidy plans and which groups the government subsidy plans should target. Considering the consumers' discount perception and uncertai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…An increasing body of literature has considered consumer preference and its impact on supply chain operation management [24,35,41,54,59]. Due to frequent changes in consumer preference, Wu and Lai [48] found that more and more firms continuously introduce new products to meet the desires of consumers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An increasing body of literature has considered consumer preference and its impact on supply chain operation management [24,35,41,54,59]. Due to frequent changes in consumer preference, Wu and Lai [48] found that more and more firms continuously introduce new products to meet the desires of consumers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results show that the government should increase subsidies for battery recycling of electric vehicles and urge electric vehicle enterprises to assume responsibility for battery recycling 43 . Liu et al 44 comprehensively sorted out the government subsidy objects in the CLSC. Research shows that when government funds are limited, medium subsidy levels can be set.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhao et al (2020) [58] constructed a profit distribution model and analyzed the impact of different government subsidy strategies on supply chain competitiveness. Liu et al (2021) [24] explored the production and recycling strategies under different government subsidy schemes. The results showed that subsiding the recycler can stimulate the recycling of end-of-life products and help the recycler increase profit.…”
Section: Literature Reviewmentioning
confidence: 99%